A atmosfera fílmica como consciência - Gil, Inês (2011)
The concept of "cinematic atmosphere" is complex because its analysis raises the problem of the cinematographic formal construction as inductive medium of the film atmosphere. Moreover, the proper notion of "atmosphere" reveals other concepts more or less controlled by the cinematic elements that will have all the same goal: the recognition of these concepts through the manifestation of the atmosphere.